ANTIFUNGAL PROPERTIES OF SECONDARY METABOLITES OF AZADIRACHTA INDICA AND LAWSONIA INERMIS – AN IN SILICO STUDY - Nagesh, Simhadri Vsdna; M, Muniappan; I, Kannan; S, Viswanathan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was aimed to inhibit the sulfite reductase using naturally obtained secondary metabolites of common plants Azadirachta indica and Lawsonia inermis. Methods: The active ingredients of neem and henna were selected and the.sdf files of these were downloaded from PubChem database. Converted the.sdf files to.pdb files with the help of OPENBABEL software which is prerequisite to dock. The three-dimensional structure was incurred from the template of homology of sulfite reductase using MODELLAR software version 9.0. Docking of sulfite reductase with the ligands was performed using iGEMDOCK and Autodock Vina softwares. The physicochemical, pharmacokinetic, drug-likeness, lead-likeness, and toxicological properties were obtained by SWISSADME and admetSAR online tools. Results: The active ingredients show an excellent affinity with the sulfite reductase which obtained was tabulated and the significant properties of a ligand were showing that these can be an investigational new drug entity. Conclusion: In this research, it can concluded that the secondary metabolites obtained from plants were inhibiting the induction of sulfite reductase thereby inhibiting Sulfite Assimilation Pathway leads to commove the amino acid metabolism of organism which shows unique in fungi.